Metabolic, Physiological, And Behavioral Responses Of Prey To Predation - Trone, Richard (East Carolina University, 2015)
Predators are known to cause prey to alter their morphology, life history or behavior in ways that reduce the likelihood of the prey being consumed by the predator. Seldom considered, however, are the consequences of predators on internal morphology (e.g., gut length) or physiology of prey. Such consideration is important because these traits likely affect prey growth and could explain why prey often grow more slowly in the presence of predators. Furthermore, a history of exposure to predators may alter how strongly visual or chemical signals from predators affect prey physiology and behavior. I raised larval frogs in artificial ponds that either lacked or contained a caged fish predator and assessed whether rearing environment affected prey gut length, morphology, behavior, and metabolic rate. I also assessed whether the rearing environment affected the metabolic and behavioral response of larval frogs to either short-term visual or chemical signals from fish by measuring the metabolism and behavior of predator naïve and predator exposed larval frogs when exposed to short-term visual and/or chemical signals from fish. Tadpoles raised with predators had shorter guts but long-term predator exposure had no effect on the metabolic rate of tadpoles, body mass, or survival. The effect of long-term predator exposure on tadpole shape depended on body size. Occurrence of predators caused tadpole shape to differ for both small and large tadpoles but not tadpoles of the average body size. Short-term exposure to chemical cues from predators altered the metabolic rate of naïve tadpoles but not tadpoles with prior exposure to predators. Smaller naïve tadpoles reduced their metabolic rate but larger naïve tadpoles enhanced their metabolic rate in response to short-term chemical cues. Chemical cues caused the metabolic rate of naïve tadpoles to be 24% greater than that observed in tadpoles that were reared with predators. Short-term visual cues did not influence the metabolic rate of any tadpoles. Prior exposure to predators did not cause tadpoles to differ in their activity levels or their likelihood to seek a refuge. Exposure to short-term chemical cues increased the number of naïve tadpoles seeking a refuge. Short-term visual cues resulted in more predator exposed tadpoles hiding in a refuge. My results indicate that long-term exposure to predators may compromise the ability of prey to extract resources by causing prey to develop shorter guts. These results further suggest the greater activity of predator exposed tadpoles to be a result of a less efficient digestion system requiring increased foraging effort but the risk of increased activity in the face of predation may be mitigated to some degree by modifications to body shape. This study supports the idea that there are complex interactions among physiology, behavior, and morphology in predator-prey interactions.
Keywords: Biology; Ecology; Physiology; Geometric morphometrics; Inducible defense; Metabolic rate; Rana sphenocephala; Tadpoles; Phenotypic plasticity; Predation (Biology); Rana